The secret history of the white-staff, being an account of affairs under the conduct of some late ministers, and of what might probably have happened if Her Majesty had not died. [By D. Defoe] (Baker)
1. 1714. 71 p. 2. 2nd ed. 1714. 72 p. 3. 1715. 80 p.